EMPLOYEE PERFORMANCE EFFECTIVELY INFLUENCED BY MOTIVATION AND WORK DISCIPLINE - Mohammad Noor Khairullah (Bajang Institute, 2023)
The purpose of this study was to determine the effect of work motivation and discipline on the performance of SMA NEGERI 1 TEMPEH Lumajang employees, either partially or simultaneously. The population in this study were all employees of SMA NEGERI 1 TEMPEH Lumajang. The number of samples in the study were 32 respondents. The sampling technique used is the census sample. The research method used is a quantitative research method using data analysis techniques used is multiple linear regression. Data collection method used in this study using a questionnaire. The results showed that the motivational variable did not have a partial significant effect on employee performance. Then for the work discipline variable it does not have a partial significant effect on employee performance. While simultaneously the variables of motivation and work discipline have a significant effect on employee performance. For SMA NEGERI 1 TEMPEH Lumajang, suggested that more often to provide motivation, especially for employees so that they can spur and encourage them to do a good job.